PROGRAM PEMBIASAAN RELIGIUS DALAM MENUMBUHKAN KARAKTER RELIGI SISWA SD MUHAMMADIYAH KETANGGUNGAN - Irfan Maulana; Moh. Toharudin; Novi Yuliyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of a religious habituation programs in fostering students’ religious character at SD Muhammadiyah Ketanggungan. The approach used is qualitative with a case study method, involving grade II students as the main subjects. Data collection techniques include observation, interviews, and documentation. The results show that habituation programs such as duha prayer, congregational Dhuhr prayer, and memorization of Quranic surahs are effective in forming students` religious habits and increasing their discipline and sense of respondsibility. The role of teachers is crucial in guiding, directing, and nurturing students. However, several obstacles were found, such as lack of enthusiasm, poor discipline, and limited understanding of the meaning of religious activities. To overcome these, teachers applied a personal approach and conducted evaluation. These evaluation served as a basis for designing appropriate teaching strategies and further actions to improve the program`s effectiveness. This study concludes that the success of religious habituation programs is highly dependent on the synergy between teacher, students, and parents.